2012
DOI: 10.1371/journal.pone.0045001
|View full text |Cite
|
Sign up to set email alerts
|

The Adult Cystic Fibrosis Airway Microbiota Is Stable over Time and Infection Type, and Highly Resilient to Antibiotic Treatment of Exacerbations

Abstract: Cystic fibrosis (CF) is characterized by defective mucociliary clearance and chronic airway infection by a complex microbiota. Infection, persistent inflammation and periodic episodes of acute pulmonary exacerbation contribute to an irreversible decline in CF lung function. While the factors leading to acute exacerbations are poorly understood, antibiotic treatment can temporarily resolve pulmonary symptoms and partially restore lung function. Previous studies indicated that exacerbations may be associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
308
3
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 333 publications
(362 citation statements)
references
References 59 publications
(108 reference statements)
36
308
3
8
Order By: Relevance
“…The Human Microbiome Project, a National Institutes of Health-sponsored initiative launched in 2007, applying culture-independent methods to assess bacterial ecology, has significantly broadened this view. Numerous studies now provide compelling evidence that the airways of persons with CF may be inhabited by diverse bacterial communities composed of dozens of species (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In addition to "typical" CF pathogens, "nonpathogenic oral bacteria," including many obligate and facultative anaerobic species, are often present in densities that well exceed those of the traditional opportunists associated with CF (4).…”
Section: The Lung Microbiome In Cfmentioning
confidence: 99%
See 2 more Smart Citations
“…The Human Microbiome Project, a National Institutes of Health-sponsored initiative launched in 2007, applying culture-independent methods to assess bacterial ecology, has significantly broadened this view. Numerous studies now provide compelling evidence that the airways of persons with CF may be inhabited by diverse bacterial communities composed of dozens of species (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In addition to "typical" CF pathogens, "nonpathogenic oral bacteria," including many obligate and facultative anaerobic species, are often present in densities that well exceed those of the traditional opportunists associated with CF (4).…”
Section: The Lung Microbiome In Cfmentioning
confidence: 99%
“…Fodor and colleagues (15) showed that bacterial community richness decreased transiently with antibiotic therapy but rebounded quickly thereafter. Zhao and colleagues (23) similarly showed a significant decrease in diversity with antibiotic therapy of exacerbation but did not find significant changes in diversity when comparing samples from periods of clinical stability to those taken at the onset of exacerbation symptoms, a finding that was subsequently confirmed in a larger study (28).…”
Section: The Lung Microbiome In Cfmentioning
confidence: 99%
See 1 more Smart Citation
“…In cystic fibrosis, changes in bacterial diversity are associated with disease progression and consequent colonization with pathogens (22). Diversity of airway microbiota in cystic fibrosis has been found to decrease significantly with disease stage (22,23). Also, the composition of the airway microbiota before an exacerbation event may be relevant to determine the microbial constituents involved in the exacerbations (24).…”
Section: State Of the Art S22mentioning
confidence: 99%
“…À côté de P. aeruginosa, d'autres espèces ou genres (Streptococcus, Prevotella, Veillonella, Rothia, Actinomyces, Gemella, Granulicatella, Fusobacterium, Neisseria, Atopobium, etc.) ont été identifiés comme étant importants dans la constitution du microbiote pulmonaire au cours de la mucoviscidose [9,11,[13][14][15][16][17][18][19][20]. L'ensemble de ces études tend à montrer qu'il existe une corrélation significative entre la diversité du microbiome pulmonaire et l'âge, le statut clinique et l'état de la fonction pulmonaire des patients [11, 15-17, 20, 26].…”
Section: Microbiome Pulmonaire Et Mucoviscidoseunclassified